The Hydration Rate of EFB-Cement Mixture Based on Different Sodium Hydroxide Concentrations - Azhan, Azrina; Nik Soh, Nik Mohd Zaini (Recent Trends in Civil Engineering and Built Environment, 2024)
One of Malaysia's most important crops is Oil Palm Empty Bunch Fiber (EFB). EFB is created when palm oil is extracted from fresh fruit bunches. Waste management issues will arise as a result of the excess waste produced by the residues of empty fruit bunches. EFB waste may be processed into fibres that provide long-lasting large-scale waste and make it suitable for cement-based products. The main objectives of this research are to determine the hydration rate for EFB-cement mixture based on different NaOH concentration, and to evaluate the effect of hydration rate of cement-EFB mixture on physical properties of empty fruit bunch fiber cement boards. This study aims to determine the appropriate proportion of sodium hydroxide (NaOH) treatment for EFB fiber in order to improve cement compatibility. The main materials use in this study are EFB, cement and water. These materials will mix together to obtain an experimental sample. Then, data logger and thermal cooper was use to ensure the temperature release by mixture cement and fiber. In this study, NaOH concentrations of 0%, 1%, 2%, 3%, 4%, and 5% are use to chemically process EFB fibers for surface morphology observation, tensile strength test and hydration rate monitoring. The result from the study found that pretreatment of EFB fibre eliminates a large proportion of silica bodies and improves the fibre's workability. When the concentration of NaOH reaches 5%, the number of silica bodies decreases and the hydration temperature of the mixture rises. When the fibre is exposed to greater concentrations of NaOH which is 5% and above, the tensile strength falls owing to lignocellulose breakdown and fibre surface rupture. Keywords: EFB-cement mixture, NaOH, Hydration Rate, Surface Morphology, Tensile Strength